Research of strategic aspects of interaction of government bodies and enterprise structures for ensuring economic development of the region - F. F. Anyurov (Путеводитель предпринимателя, 2020)
In article provisions on making decision on a choice of strategy of development of the company are developed, the multicomponent assessment as the tool of a choice of a priority format of cooperation of business and the power is offered, the model of influence of a multugruppa on development of regional economy is developed.